Examining the relationship between toxic leadership, behavioural cynicism, employee well-being, and emotional exhaustion: The mediating role of employee silence - Aslan, Ahmet; Aslan, Ahmet (My University, 2025)
Employees often perceive toxic leader behaviours such as arrogance, manipulation, and hypersensitivity as indicators of imbalance and injustice in the leader-employee relationship. This imbalance can suppress employee voice and contribute to adverse workplace outcomes, including behavioural cynicism, emotional exhaustion, and diminished well-being. This study investigates the mediating role of employee silence in the relationship between toxic leadership and three key outcomes: organisational cynicism, emotional exhaustion, and employee well-being. Data were collected from 414 employees working in hotel businesses in Turkey using a structured questionnaire. A quantitative research design was employed, and the relationships among variables were tested through structural equation modelling using Jamovi (version 2.6.26) software. The results indicate that employee silence partially mediates the effect of toxic leadership on both behavioural cynicism and emotional exhaustion. Furthermore, employee silence fully mediates the relationship between toxic leadership and employee well-being. These findings underscore the crucial role of silence as a psychological mechanism linking toxic leadership to employee outcomes in high-pressure service environments, such as the tourism sector.
Keywords: Toxic Leadership; Emotional Exhaustion; Hotel Employees; Employee Well-Being; Employee Silence; Behavioural Cynicism